Erratum: ANDREA PARIMUCHOVÁ & ĽUBOMÍR KOVÁČ (2016) Redescription of two troglobiotic species of Deuteraphorura Absolon, 1901 (Collembola, Onychiuridae) from the Western Carpathians. Zootaxa, 4168: 327–340. - Parimuchová, Andrea; Kováč, Ľubomír (Zootaxa, 2017)
N/A